2017
DOI: 10.1103/physrevd.96.034027
|View full text |Cite
|
Sign up to set email alerts
|

Single spin asymmetries in forward pp/A collisions revisited: The role of color entanglement

Abstract: We calculate the single transverse spin asymmetries(SSA) for forward inclusive particle production in pp and pA collisions using a hybrid approach. It is shown that the Sivers type contribution to the SSA drops out due to color entanglement effect, whereas the fragmentation contribution to the spin asymmetry is not affected by color entanglement effect. This finding offers a natural solution for the sign mismatch problem.PACS numbers: Keywords:I. Introduction. -During the past three decades, the studies of tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In the coherent QCD multiple scattering framework [42], it has been shown that at low p T the rates of single and double hadron production are highly suppressed and the amount of suppression grows with rapidity and centrality; meanwhile, at high p T , such nuclear modification effects become less pronounced as we enter the perturbative region in a dilute nuclear medium. For the computation of TSSA's, a hybrid approach has been widely used in photon, γ-jet and dijet production [43][44][45][46]. The hybrid approach treats the gluon distribution inside the heavy nucleus in the CGC framework and utilizes the twist-3 formalism for the proton side.…”
Section: Introductionmentioning
confidence: 99%
“…In the coherent QCD multiple scattering framework [42], it has been shown that at low p T the rates of single and double hadron production are highly suppressed and the amount of suppression grows with rapidity and centrality; meanwhile, at high p T , such nuclear modification effects become less pronounced as we enter the perturbative region in a dilute nuclear medium. For the computation of TSSA's, a hybrid approach has been widely used in photon, γ-jet and dijet production [43][44][45][46]. The hybrid approach treats the gluon distribution inside the heavy nucleus in the CGC framework and utilizes the twist-3 formalism for the proton side.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the CGC framework, the two most relevant quantities are given by the saturation scale Q s and the coupling strength α s , which determines the initial population density ∼ 1/α s of the initial state. As an initial non-equilibrium isotropic profile for gluons, formed at time scales ∼ 1/Q s , one usually considers a step function of the form f init (p) = d g f 0 Θ(1 − p/Q s ), whereby f 0 ∼ 1/α s [8,15,16,18]. However, we use a similar function with a smooth tail around p ≈ Q s .…”
Section: Initial Conditionmentioning
confidence: 99%
“…To overcome this issue we extract effective values for the chemical potential µ eff and the temperature T eff by fitting the IR region ( f IR (p < m)) of the distribution function to the Bose-Einstein distribution function. If now µ eff approaches m (let us name this point in time t onset ), we manually insert a finite but negligibly small seed to the zero mode n c (t = t onset ) = 10 −6 n init [15,16,18,25].…”
Section: Initial Conditionmentioning
confidence: 99%
See 2 more Smart Citations